Kidney Injury, Insulin Therapy, and Hypoglycemia - Roland N. Dickerson, (Journal of Pharmacy and Nutrition Sciences, 2012)
The intent of this review is to evaluate the literature with respect to increased risk for hypoglycemia for critically ill patients with acute kidney injury or chronic kidney disease who are given insulin therapy. The unique pathophysiology of insulin and glucose metabolism during renal failure that predisposes patients for hypoglycemia is reviewed. Studies that contribute to the understanding and clinical relevance of renal dysfunction upon glycemic control during intensive insulin and continuous nutrition therapy are evaluated. Some practical suggestions for management of hyperglycemia with insulin therapy for critically ill patients with renal failure are given.